THE OPERATED GEAR STEP OF THE CRANE REDUCER - Yu. V. Remizovich; O. V. Abdulaeva (Вестник СибАДИ)
In this article the design of a gear step of a crane reducer supplied with the coupling and the mechanism of inclusion and intended for transfer considerable (>10 kNm) the rotating moments is offered. The coupling which is built in a wheel contains two rows of conic rollers, the maple couple put in action by the step electric motor via the ball screw gear. Recommendations about calculation are made.